2020
DOI: 10.21203/rs.3.rs-32517/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sociodemographic profile, clinical characteristics, anxiety, and depression of 74 patients infected with COVID-19: first report from Bangladesh

Abstract: Background: The pandemic of Corona Virus Disease 2019 (COVID-19) has cost a large number of lives and is causing substantial mental stress among people. We conducted a study to identify the sociodemographic and clinical characteristics and prevalence of anxiety and depression among confirmed COVID-19 cases in Bangladesh.Methods: An online cross-sectional survey using a preformed questionnaire adapted in Google form was conducted for data collection. The form was shared along with a brief introduction and ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Higher age range is probably the affected older aged family members of the patient. Like other studies 11,7,[12][13][14] from home and abroad male were more than female in our study. MERS-CoV and SARS-CoV had a similar pattern of sex distribution.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Higher age range is probably the affected older aged family members of the patient. Like other studies 11,7,[12][13][14] from home and abroad male were more than female in our study. MERS-CoV and SARS-CoV had a similar pattern of sex distribution.…”
Section: Resultssupporting
confidence: 82%
“…In our study we have studied of 305 RT-PCR positive COVID-19 patients. Mean age of the patient was 36.32(+/-12.369) years; another study 11 from our country showed mean age was 42.59±14.43 years. Data from the Institute of Epidemiology, Disease Control, and Research (IEDCR) 10 revealed that 42% of the Bangladeshi COVID-19 cases were aged between 21 and 50 years but in our study age range was 17-78 years.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations